PENGARUH UKURAN SEL TERHADAP HASIL PREDIKSI MODEL AGNPS DALAM EVALUASI PENGENDALIAN KUALITAS PERAIRAN DARI SUMBER PENCEMAR PERTANIAN - Nugroho, Sutopo Purwo (Jurnal Teknologi Lingkungan, 2000)
Water quality monitoring effort increased with concern about protection ofthe water quality from waterbody. AGNPS model, which was developed toobjectively evaluate alternative land management strategies on non point source pollution from agricultural watersheds, offers a method of predicting the quality of water from the watershed. The model has the ability to output water quality characteristics at intermediate points throughout the watershed network. The size cell was very influence the result of output model. More large of the size cell so the sediment and nutrient yield output was large too. Scale of map for indentify the input model was influnce the result of output model.